The Use of Sustainability Management Accounting Information Systems for Decision Making in Government Organizations - Renal Pradisti; Sri Adelia Bailia; Riflah Salsabila R. Hi. Wahid; Rania Mutiara Tirza; Jamaluddin; Ernawaty Usman; Rahmi Syafitri (Journal of Economics and Business, 2026)
This study examines the role of the Sustainability Management Accounting Information System (MAIS) in supporting decision-making within government organizations through a descriptive qualitative approach based on a literature review and document analysis. The results show that MAIS provides relevant, accurate, and timely financial data, thereby improving the quality of local government financial reports, transparency, and public accountability as pillars of good governance. The effectiveness of MAIS is influenced by human resource capacity, institutional commitment, leadership support, and an adaptive organizational culture. Challenges include resistance to change, budget constraints, and data security. Therefore, the continuous development and improvement of civil servant competencies are strategic steps toward effective, transparent, and accountable governance.